Pt- and Ru-doped SnO2-Sb anodes with high stability in alkaline medium - Berenguer, Raúl (2014)
Different Pt- and Ru-doped Ti/SnO2-Sb electrodes were synthesized by thermal decomposition. The effect of the gradual substitution of Sb by Ru in the nominal composition on the physicochemical and electrochemical properties were evaluated. The electrochemical stability of the electrodes was estimated from accelerated tests at 0.5 A cm-2 in 1 M NaOH. Both as-synthesized and deactivated electrodes were thoroughly characterized by scanning electron microscopy (SEM), energy-dispersive X-ray microanalysis (EDX), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and X-ray diffraction analysis (XRD). The incorporation of a small amount (about 3 at. %) of both Pt and Ru into the SnO2-Sb electrodes produced a 400-times increase in their service life in alkaline medium, with no remarkable change in the electrocatalysis of the oxygen evolution reaction (OER). It is concluded that the deactivation of the electrodes is promoted by alkaline dissolution of metal species and coating detachment at high potentials. The introduction of Pt has a coating compacting effect, and Ru(IV), at low amounts until 9.75 at. %, replaces the Sn(IV) cations in the rutile-like SnO2 structure to form a solid solution that strongly increases the stability of the electrodes. The observed Ru segregation and decreased stability for larger Ru contents (x > 9.75 at. %), together with the selective dissolution of Ru after deactivation, suggest that the formation of a homogeneous (RuδSn1-δ)O2 single-phase is crucial for the stabilization of these electrodes.